Hukum Kontrak Ba'i ibn al-Arabi dan Relevansinya Pada Masalah Maliah Muamalah Kontemporer - Enang Hidayat; Abu Umar Faruq Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The legal maxims of the ba'i contract are inductive Islamic legal reasoning, so their implementation has a static and dynamic character. Apart from al-Arabi, attention to two characters in one theme of fiqh (Islamic Jurisprudence) rules is rarely discussed by Islamic jurists. It is one of the reasons for the failure to dynamize the theory and practice of Islamic economic law, resulting in various criticisms. This research discussed the legal maxims of the ba'i contract of al-Arabi in Al-Masalik fi Syarh Muwatta Malik and their relevance to contemporary muamalah maliah issues to provide complete answers to various criticisms in contemporary Islamic legal theory and practice. The research method used normative Islamic law with a conceptual, philosophical, and historical approach. The data collection technique used a document study of Ibn al-Arabi's work